Mehregan, I., Younesi, S. & Liden, M. (2021). Donysia avia (Primulaceae), a new species from Zagros Mountains (Iran). Phytotaxa 511 (3): 296–300. - Mehregan, Iraj; Younesi, Simin; Lidén, Magnus (Phytotaxa, 2021)
Erratum